2021
DOI: 10.1021/acsabm.1c00445
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Iridium(III) Complex-Sensitized NiO-Based-Cathodic Photoelectrochemical Platform for DNA Methyltransferase Assay

Abstract: This work reports an efficient [(C6) 2 Ir(dppz)] + PF 6 − (C6 = coumarin 6 and dppz = dipyridophenazine)-sensitized NiO photocathode and its application in photoelectrochemical (PEC) bioanalysis field for the first time. This dye-sensitized NiO photocathode was found to exhibit a markedly enhanced cathodic photocurrent. A sensitive cathodic PEC platform was proposed integrating the as-prepared photocathode with enzyme-free cascaded amplification strategies of the catalytic hairpin assembly (CHA) and the hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In addition, it can selectively detect M.SssI in human serum samples and evaluate the efficiency of M.SssI inhibitors, which is a good reference for the detection of clinical samples. Cai et al 77 reported for the first time an efficient [(C6) 2 Ir(dppz)] + PF 6 À (C6 = coumarin 6, dppz = dipyridazine) sensitized nickel oxide photocathode and its application in photoelectrochemical (PEC) bioanalysis (Fig. 1(F)).…”
Section: Hybridized Strand Reaction (Hcr)mentioning
confidence: 99%
“…In addition, it can selectively detect M.SssI in human serum samples and evaluate the efficiency of M.SssI inhibitors, which is a good reference for the detection of clinical samples. Cai et al 77 reported for the first time an efficient [(C6) 2 Ir(dppz)] + PF 6 À (C6 = coumarin 6, dppz = dipyridazine) sensitized nickel oxide photocathode and its application in photoelectrochemical (PEC) bioanalysis (Fig. 1(F)).…”
Section: Hybridized Strand Reaction (Hcr)mentioning
confidence: 99%